AN ANALYSIS OF HIGHER ORDER THINKING SKILL QUESTIONS IN READING COMPREHENSION IN SCHOOL FINAL EXAMINATION IN BIMA - Novi Sri Rahmi; Nizam Ahsani (Journal of Social and Economics Research, 2023)
This study is aimed at finding out the distribution of higher order thinking skill questions, describing the specific cognitive processes demonstrated under HOTS questions, and finding out the portion of HOTS questions in two school examination packages in Bima. Content analysis was used to examine 86 reading comprehension test items in school final examination using Bloom’s taxonomy revised version. Qualitative data analysis was applied to the reading comprehension question items. Public documentation, indirect observation and a semi-structured interview were performed to collect the data. Data source were collected from reading comprehension test items and analysis card. In analyzing the data, qualitative analysis of Miles, Huberman, & Saldana (2014) model with three phases was applied. The findings indicated the distribution of higher order thinking skill questions are lower than lower order thinking skill questions. HOTS only obtain 6 out of 86 questions while the rest of questions are indicated as LOTS. Analyze skill has the highest distribution among HOTS skills: 4 questions, evaluate skill has 2 questions, while create skill is not found. On the contrary, the most used specific cognitive processes in the whole questions are interpreting and recognizing skill with the frequency of 18 questions, and differentiating and critiquing skills frequently appear in the test as the specific cognitive processes of HOTS questions